The Analysis of the Exegesis of the Quran Verse of Hadd Punishment for Theft through the Verse “أَنَّ الْمَسَاجِدَ لِلّٰهِ” - Mahdi Ebadi; Sayyed Muhammad Mortazavi; Muhammad Ebrahim Roshanzamir (آموزه‌های قرآنی, 2018)
One of the most efficient and best methods of the Quran Exegesis is to use the noble Quran for its exegesis. The exegetes of the noble Quran through the Quran have advanced proofs for the authenticity and validity of this method and they have believed this method is taken from the manner of the infallibles. The holy Quran verse about stealing (Surat Al-Ma'idah/38) is of the most prominent instances of this manner which has been taken by the exegetes and according to this, the didactic aspect of this manner in the exegetical traditions of Ahl al-Bayt has been reached to the stage of emergence and proving by them. But it should be considered that all the Quran exegetical traditions through the Quran have not had the didactic aspect and there are some other faces in them. Although in the tradition of Imam Javad (peace be upon him), the stealing verse has been interpreted through the verse أَنَّ الْمَسَاجِدَ لِلهِ (Surat al-Jinn/18) and the amount of cutting off hands are determined according to it. But the study shows that this hadith has no the didactic aspect and for silencing the opponents and proving the legislated hukm, Imam has merely caused to be understood the meaning of the Quran stealing verse through the interpretation and requirements of meaning of one verse (Surat al-Jinn/18). The other hadiths for the interpreting this verse for the interpretation of the Quran stealing verse and by adducing the other verses (determining the other evidences) for the exegesis of the mentioned verse and also the exegetical examination of the terms “ید” (hand) and “مساجد” (mosques) support this issue. In addition to these subjects, really, the components of the theory of the exegesis of the holy Quran through the holy Quran believe that fiqhi ordinances are out of the inclusion of the Quran exegesis through the Quran and are of exceptions